(untitled) (Research, Society and Development, 2019)
The curricular proposal of the State of São Paulo (Brazil) suggests for Elementary Education in the discipline of Sciences contents related to Astronomy. In a public basic school in Santo André, an analysis was realized to examine the previous knowledge of three classes of the 6th year. Only 19,0% of the students reached the minimal satisfactory note. In the same year, the contents were presented with different teaching strategies. In one class, an expository lesson with audiovisual aids was applied, in a second class an expository lesson with dialog and in the third one, a research by means of didactical books was conducted, elaborated using instruments and signs of agreement the intellectual development proposed by Vygotsky. The case study methodology was used to investigate and analyze the students’ performance and analysis of variance (ANOVA) to test which strategy was most efficient. After the approach, it was observed that there was an improvement in the performance of the pupils, however the statistical difference between the three strategies was not significant. By this study it became possible to undertake analyses of learning and teaching strategies to improve the astronomy education in the discipline of science.